Analysis of Communication Terms in the Qur'an and Their Application in Qur'an-Based Learning - Gamal Abdel Nasier (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
This study aims to analyze the communication terms contained in the Qur'an. The term is presented denotatively and connotatively. The denotative categories that will be presented include: Qâulan Baligha (QS. An-Nisa': 63), Qâulan Layyina (QS. Thaha: 44), Qâulan Ma'rufa (QS. Al-Baqarah: 235; QS. An-Nisa' : 5 & 8; QS. Al Ahzab: 32), Qâulan Maisura (QS. Al-Isra': 28), Qâulan Karima (QS. Al-Isra': 23). While the terms of communication that fall into the category of connotative understanding include the following; Mau'idhah (An-Nisa': 66), Da'wah: (An- Nahl: 125; Yusuf: 108), Nashihah (al-A'raf: 21, 62, 68, 79), Tausiyah (al-Ashr : 3). In this study the authors used a qualitative descriptive method through literature review. The results of this study indicate that all the communication terms offered by the Al-Qur'an are ways of communication that must be mastered by educators so that in learning activities communication is carried out with words that make an impression on the heart, say softly, say kindly and firmly, say what is appropriate, glorify those invited to communicate, able to provide teaching when speaking (beneficial for the listener), there is advice contained in the words, invites kindness and advises one another. This study provides an in-depth understanding of communication terms in the Quran, identifies their denotative and connotative categories, and presents the application of Islamic communication principles in the learning process. The results are expected to serve as a basis for educators and teachers in implementing effective communication based on Quranic values in educational activities.